2000
DOI: 10.3138/cmlr.57.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Challenges for Language Learners in Job-Training Programs

Abstract: This paper describes a study carried out in a pre-apprenticeship job-training program held at a community college in central Canada, in which learners from a variety of language backgrounds were enrolled. Through a combination of student questionnaires, learner interviews, and participant observation in the classroom, information was gathered on factors affecting progress in such programs. The article describes the language and literacy challenges encountered by the learners in relation to the Luke and Freebod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…During our observations in the cohort-based program, it was noted that many teachers were reluctant to use teaching aids such as slides. As is documented elsewhere (Bell, 1994(Bell, , 2000, technical instructors appeared to believe that "good teachers" were capable of delivering lecture s without notes or slides. It was implied that those faculty members who did make use of audiovisual aids were failing to do adequate preparation themselves and instead relying on commercial props.…”
Section: Suggestions For Improvementmentioning
confidence: 97%
See 1 more Smart Citation
“…During our observations in the cohort-based program, it was noted that many teachers were reluctant to use teaching aids such as slides. As is documented elsewhere (Bell, 1994(Bell, , 2000, technical instructors appeared to believe that "good teachers" were capable of delivering lecture s without notes or slides. It was implied that those faculty members who did make use of audiovisual aids were failing to do adequate preparation themselves and instead relying on commercial props.…”
Section: Suggestions For Improvementmentioning
confidence: 97%
“…The student groups were predominantly male and were drawn almost entirely from those whose educational and workforce experiences have been somewhat unsuccessful. As acknowledged earlier, the two programs were held in different locations and comments made may reflect some of the ethnic and linguistic differences of the local populations (see Bell, 2000, for a related discussion). Future work which examines actual measures of success on specific outcomes such as securing successful employment in the field is obviously indicated as this study was focused primarily on student perceptions of program effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a much more intensive commitment of time (some 80 days of data collection spread over a 1-year period, plus weeks of transcription, analysis, participant review, etc. ), my study of Phil's program generated only two published pieces (Bell, 2000;2003), of which only one was accepted by a refereed journal. Some of this limited output may reflect my struggle with the ethical issues or just personal dilatoriness, but the logistics of narrative studies also played a part.…”
Section: Publishing the Researchmentioning
confidence: 99%
“…These differences can frequently lead to misunderstanding, frustration, or simply feelings of inadequacy that may put intercultural newcomers’ academic success at risk. Researchers have found that culturally incongruent classroom language practices tend to prevent minority students from participating effectively in teacher‐planned learning activities (Bell, 2000; Crago, 1992; Holmes, 2006; Lantolf & Genung, 2002). Students may fail to benefit from instructional activities not in line with their own cultural practices.…”
Section: Symbolic Power Of Communicative Skills and Cultural Competencementioning
confidence: 99%